2023
DOI: 10.3389/fbioe.2023.1140436
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel systems for targeted cancer therapy

Abstract: When hydrogel materials with excellent biocompatibility and biodegradability are used as excellent new drug carriers in the treatment of cancer, they confer the following three advantages. First, hydrogel materials can be used as a precise and controlled drug release systems, which can continuously and sequentially release chemotherapeutic drugs, radionuclides, immunosuppressants, hyperthermia agents, phototherapy agents and other substances and are widely used in the treatment of cancer through radiotherapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 129 publications
0
15
0
Order By: Relevance
“…Whereas the former can suffer from low biocompatibility and nonspecific accumulation, 18 hydrogel-based systems offer a biocompatible drug delivery method for controlled and localized release that allows for minimized drug content and systemic toxicity. 19,20 Several macroscopic hydrogels�for in situ implantation/ injection or transdermal delivery�have been developed for improved chemotherapeutic efficacy. 21 In cases that bypass surgical intervention via in situ injection, researchers have relied on self-assembled or cross-linked polymer or polymerhybrid systems and have used targeting moieties and loaded immunotherapeutics to improve their efficacy.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the former can suffer from low biocompatibility and nonspecific accumulation, 18 hydrogel-based systems offer a biocompatible drug delivery method for controlled and localized release that allows for minimized drug content and systemic toxicity. 19,20 Several macroscopic hydrogels�for in situ implantation/ injection or transdermal delivery�have been developed for improved chemotherapeutic efficacy. 21 In cases that bypass surgical intervention via in situ injection, researchers have relied on self-assembled or cross-linked polymer or polymerhybrid systems and have used targeting moieties and loaded immunotherapeutics to improve their efficacy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These materials often take the form of nanoparticles or hydrogel-based systems. Whereas the former can suffer from low biocompatibility and nonspecific accumulation, hydrogel-based systems offer a biocompatible drug delivery method for controlled and localized release that allows for minimized drug content and systemic toxicity. , …”
Section: Introductionmentioning
confidence: 99%
“…19 It has been shown that grafting adipic acid dihydrazide (ADH) onto the carboxyl group of hyaluronic acid (HA) formed a coupled reagent (HA-ADH) with excellent biocompatibility and sensitive pH responsiveness. 20,21 Park JK et al 22 reported a composite film based on poly(lactic-co-glycolic acid) (PLGA), HA, and ADH. This film may be used as a periodontal barrier film to promote bone regeneration in patients with periodontitis due to its excellent biocompatibility and controlled biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, biodegradable hydrogels have gained increasing recognition for their applications in cancer treatment. [ 29 ] Among them, thermosensitive hydrogels with sol–gel phase transition characteristics are particularly well‐suited as delivery platforms for achieving sustained release of therapeutic agents at localized sites. [ 30,31 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, biodegradable hy-drogels have gained increasing recognition for their applications in cancer treatment. [29] Among them, thermosensitive hydrogels with sol-gel phase transition characteristics are particularly wellsuited as delivery platforms for achieving sustained release of therapeutic agents at localized sites. [30,31] In this present study, we designed an injectable nanoparticles (NPs)-hydrogel composite system (designated as LOX-MnO 2 @Gel) for intratumoral catalytic depletion of lactate.…”
Section: Introductionmentioning
confidence: 99%